连续油管注入头链条系统力学分析 - 许立; 朱万鑫; 施志辉 (Jixie chuandong)
The rollers of chain system are main parts under stress in coiled tubing injector and are often damaged in use.The chain system using in different clamping ways are analyzed through multibody dynamic analysis software ADAMS.According to the relative position between roller and other members when appearing maximum load in the roller centroid,the load variation of roller centroid in different chain systems and damage courses are obtained.Through ANSYS finite element contact analysis of chain roller & sprocket and floating platen & chain roller,the contact stress distributions of chain roller &sprocket and floating platen &chain roller are obtained.The roller that contacts floating platen is easily damaged by the analysis results.The above results can provide theoretical basis for optimization design of chain system.